Preparation of poly(ethylene glycol) brushes on polysulfone membranes for olefin/paraffin separation - Park, YS; Won, J; Kang, YS (AMER CHEMICAL SOC, 2000)
Thin solvent-free polymer electrolytes containing silver salts showed a facilitated transport of propylene. Poly(ethylene glycol) (PEG) was immobilized on a polysulfone (PSf) membrane surface and subsequently complexed with AgBF4, which can be used as a membrane for the separation of olefin/paraffin mixtures. Photoreactive azidophenyl group was bound to the chain terminus of PEG, and the modified PEG was immobilized onto the surface of the PSf microporous membrane by ultraviolet irradiation. The propylene permeance was increased for the PEG brush membrane complexed with silver salt. The propylene permeance was 95 gas permeance units and the propylene selectivity over propane was 12 when the theoretical mole ratio of silver to ethylene oxide unit reached 1. Excellent propylene transport performance is attributed to the thin layer of PEG as well as the high loading of silver ion, the propylene carrier, in the thin PEG matrix.
Keywords: POLY(PROPYLENE OXIDE); MOLECULAR-WEIGHT; COMPLEXES; POLYMER; ELECTROLYTES; THIOCYANATE; TEMPERATURE; TRANSPORT; SODIUM